IMPLEMENTASI STRATEGI PEMBELAJARAN KONTEKSTUAL OLEH GURU PAI DALAM INTERNALISASI KARAKTER SISWA YANG BERBUDI LUHUR DI SMA N 01 KAJEN - Kistanti; Sasa Refiatul Alfianti; Rosalina; Nur Laila Ana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Islamic Religious Education (PAI) plays a strategic role in shaping students' personalities and characters in line with Islamic values, not just limited to cognitive aspects. However, the main challenge arises in students' ability to implement and actualize these values in everyday life. Therefore, a learning strategy is needed that can encourage students to build understanding through direct experience and reflection in real contexts. The purpose of this study is to describe the implementation of contextual teaching and learning (CTL) strategies by Islamic Religious Education teachers in internalizing virtuous character in students at SMA Negeri 1 Kajen. The study used a descriptive qualitative method with structured interviews as the data collection technique. Data analysis was carried out through the stages of data reduction, data presentation, and drawing conclusions according to the Miles and Huberman model. Based on the results of the study, the CTL strategy was implemented through strengthening real-world practices, analyzing actual phenomena, and habituating positive activities such as regular worship and environmental cleanliness. Although there were obstacles in the form of a 25% planning discrepancy due to the dynamics of adolescent social interactions and time constraints, this strategy proved effective in transforming religious theory into real-life student behavior. It can be concluded that the implementation of the CTL strategy significantly facilitates student character development by integrating knowledge, attitudes, and skills. This approach ensures that Islamic values are more firmly embedded through direct experiences relevant to everyday life.